C1 U4 BBB VWCZxa 277 Fi FH
C1 U4 BBB VWCZxa 277 Fi FH
C1 U4 BBB VWCZxa 277 Fi FH
Chapter 2 Polynomials
1. If the polynomial 3x3 - 4x2 - 17x - k is exactly divisible by x - 3, then the value of ‘k’
is (1)
a. 6
b. 5
c. -5
d. -6
2. The number of zeroes that the polynomial f(x) = (x – 2)2 + 4 can have is (1)
a. 0
b. 2
c. 3
d. 1
3. If ‘2’ is the zero of both the polynomials 3x2 + mx - 14 and 2x3 + nx2 + x - 2, then the
value of m – 2n is (1)
a. 5
b. -1
c. 9
d. -9
4. If one of the zeroes of the cubic polynomial x3 + ax2 + bx + c is –1, then the product of
the other two zeroes is (1)
a.
b.
c.
d.
5. A quadratic polynomial with zeroes and – 1 is (1)
a.
b.
c.
d.
6. If(a-b), a and (a+b) are zeros of the polynomial 2x3-6x2+5x-7, write the value of a. (1)
7. The sum of the zeros and the product of zeros of a quadratic polynomial are and
-3 respectively. Write the polynomial. (1)
8. Find the quadratic polynomial whose zeroes are and (1)
9. Sum and product of zeroes of quadratic polynomial are 5 and 17 respectively. Find
the polynomial. (1)
10. Find a quadratic polynomial whose one zero is -8 and sum of zeroes is 0. (1)
11. Find the zeros of the quadratic polynomial f(x) = abx2 + (b2 - ac)x - bc, and verify the
relationship between the zeros and its coefficients. (2)
12. Find the zeros of the following quadratic polynomials and verify the relationship
15. Find all the zeroes of p(x) = x3 - 9x2 - 12x + 20 if x + 2 is a factor of p(x). (3)
16. If α and β are the zeroes of the quadratic polynomial f(x) =6x2 + x – 2, then, find the
value of . (3)
17. Can (x – 2) be the remainder on division of a polynomial p(x) by (2x + 3)? Justify your
answer. (3)
19. Obtain all other zeroes of the polynomial x4 + 6x3 + x2 - 24x - 20, if two of its zeroes are
+ 2 and - 5. (4)
Solution
1. d. -6
Explanation: If the polynomial is exactly divisible by
, then
(By factor theorem)
2. b. 2
Explanation: = =
Here the largest exponent of variable is 2,
therefore number of zeroes of the given polynomial is 2.
3. c. 9
Explanation: According to the question,
Also
4. a.
Explanation: Let are the zeroes of the given polynomial. Given:
and To find : Since,
……….(i)
Also
[From eq. (i)]
5. a.
Explanation: x2-( )x + =0
Here And =
x2 -( )x + ( )=0
x2 + x- =0
= 0 (By L.C.M)
Now, = =3
⇒ ( a - b) + a + (a + b ) = 3
⇒a-b+a+a+b=3
⇒ 3a = 3
⇒ a = 3/3
⇒a=1
So the value of a in given polynomial is 1.
p(x) = x2 - +
Required quadratic polynomial,
p(x) = x2 - x + (-3)
= x2 + x-3
8. Sum of zeroes =
Product of zeroes =
Quadratic polynomial is x2-(sum of zeroes)x + product of zeroes
=
9. Sum of zeroes = 5
Product of zeroes = 17
= x2 - 64
11. We have,
A = ab , B= b2 - ac, C = -b
= 4 (2x2 - 1)
Sum of zeros =
Product of zeros =
Here,
= 10
and = 25 - 2 = 23
14. 0,
17. No, (x – 2) cannot be remainder on division of polynomial p(x) by (2x + 3) because the
degree of remainder is either 0 or its degree is less than the degree of the divisor.
18. P(x) = x3 + px2 + qx + 2
Here, a = 1, b = p, c = q, d = 2
Now, = -p.......(i)
=q
= q..............(ii)
and = -2
= -2.......................(iii)
Also,
Therefore, (iii) becomes -1
Substituting in (i), we get
=- p - 2
Substituting these value in (ii), we get
-1 + 2(-p - 2) = q
-1 - 2p - 4 = q
2p + q + 5 = 0
product of factors is (x - 2) (x + 5) = x2 + 3x - 10
Dividing x + 6 + - 24x - 20 by + 3x - 10
20.
By division algorithm for polynomials, we have
x2 - 5 = 0 and x2 - 2x - 3 = 0
x2 - ( )2 = 0 and x2 + x - 3x - 3 = 0
(x - )(x + ) = 0 and (x + 1)(x - 3) = 0
x= ,x=- , x = -1 and x = 3
So, the zeroes are α = , =- , γ = -1 and = 3 .